PENGARUH MODAL INTELEKTUAL TERHADAP KUALITAS LABA DENGAN MANAJEMEN LABA SEBAGAI PEMEDIASI - Ferdinandus Indra, Estralita Trisnawati (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of research is to obtain empirical evidence about the impact of intellectual capital to earnings quality with earnings management as intervening, this research used sampel as manufacture companies listed on the indonesia Stock Exchange (IDX) in 2016-2018. This study used 67 manufacture companies selected using purposive sampling method. The data used are secondary data in the form of financial statements. The statistical method used to test the research hyphotesys is the double regretion analysis model and path analysis. The result of this research show that intellectual capital has significant negative impact indirectly on earnings quality with earnings management as intervening variable in reporting and financial practices.